Produksi dan Bobot Telur Puyuh (Coturnix coturnix japonica) dengan Penambahan Tepung Daun Pepaya (Carica Papaya L.) sebagai Pakan Alternatif: Production and Weight of Quail Eggs (Coturnix coturnix japonica) with Additional Papaya Flour Leaves (Carica papaya L.) as Alternative Feed - Dahrul Ali; Intan Dwi Novieta; Sultan Mubarak Z; Fitriani Fitriani (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of adding flour papaya leaf (Carica papaya L) on egg production and weight in quail by using a completely randomized design (CRD) method with four treatments and three replications. P0: No control treatment 0%. P1: Flour papaya leaves (Carica papaya L) 1% of the amount of feed. P2: Papaya leaf flour (Carica papaya L) 3% of the total feed. P3: Papaya leaf flour (Carica papaya L) 5% of the total feed. The results showed that the addition of leaf flour at different levels had no significant effect (P> 0.05) on egg production while the egg weight had a significant effect (P<0.05). Average egg production P0 (62.5%), P1 (78.12%), P2 (79.16%), P3 (83.33%), Egg weights P0 (8.4%), P1 (9%) P2 (10.13%) and P3 (11.23%). As for the best treatment is in the P3 treatment with the addition of leaf flour papaya as much as 5%